Blunt splenic injury in a child with situs inversus totalis treated with transcatheter arterial embolization - Naoki Hashizume; Kimio Asagiri; Naoko Komatsuzaki; Suguru Fukahori; Shinji Ishii; Nobuyuki Saikusa; Naruki Higashidate; Motomu Yoshida; Saki Sakamoto; Hirotomo Nakahara; Yoshihiko Konoike; Kojiro Nagai; et al. (Elsevier, 2016)
We report the first case of blunt splenic rupture in a child with situs inversus totalis treated with transcatheter arterial embolization (TAE). A 12-year-old girl fell roughly 4 feet onto the pavement while riding her bicycle. Contrast-enhanced computed tomography revealed situs inversus totalis, a massive hemorrhage in the abdominal cavity, and a ruptured spleen with extravasation. Arteriography showed that the internal organs were located opposite their normal positioning. TAE was carried out with gelfoam and a micro coils at the branch of the upper lobe of the splenic artery. TAE is effective for blunt splenic injury with extravasation in a child with situs inversus. In TAE, there is no technical difference about situs inversus excepted mirror image of abdominal vascular formation.